Pedagogical Psychodrama: a participative technique for health promotion strategies - Canel, Regina Célia; Focesi Pelicioni, Maria Cecília (O Mundo da Saúde, 2007)
ABSTRACT: This article aims to justify the use of Pedagogical Psychodrama as an ancillary tool in practices of Health Promotion. Psychodrama facilitates knowledge transference and the acquisition of concepts. Such qualities are especially important for training and enhancing work teams and promote people’s participation and empowerment. The participation of all social actors is crucial in the elaboration of Public Policies and the development, execution, supervision and evaluation of practice for Health Promotion